Treatment options for alveolar soft part sarcoma in pediatric patients. (June 2014) - Bisogno, Gianni; Ferrari, Andrea; Alaggio, Rita; Orbach, Daniel
Abstract : Introduction: Alveolar soft part sarcoma (ASPS) is a very rare tumor in children and adolescents. It is frequently disseminated at diagnosis and metastatic relapses are frequent during follow-up. Among the various sarcomas, ASPS has a very specific clinical presentation, radiological pattern, spread and evolution. There are no established treatment guidelines; complete tumor resection gives the best chance of cure but may be unfeasible in up to 45% of patients. Conventional chemotherapy is used but with limited effect, making the search for new active agents important. Areas covered: The rarity of ASPS has made it impossible to conduct large prospective trials in adult or pediatric populations. Treatment options for ASPS are consequently discussed by analyzing the results obtained in adult and pediatric series published in the last 25 years. Expert opinion: Although marginally higher response rates have been reported in pediatric series (from 0 to 28%) than in adults (< 10%), published experiences show a very limited efficacy of conventional chemotherapy against ASPS. Response to tyrosine kinase inhibitors, such as sunitinib or cediranib, has recently been reported in adult patients and replicated in a few pediatric patients too. Given the unsatisfactory outcome of standard chemotherapy, the current treatment approach with conventional regimens (e.g., ifosfamide and doxorubicin, as used for other soft tissue sarcomas) should be reconsidered in unresectable/disseminated ASPS. The inclusion of ASPS in trials that test targeted therapies is recommended.